البناء والتركيب في رواية "طيىر التاجي" لإسماعيل فهد إسماعيل Syntax and Structure in the Novel 'Tuyoor Al- Taji' By Ismail Fahad Ismail Ilmu Linguistik dan Gaya Bahasa di Dalam Novel 'Burung-Burung Taji' oleh Ismail Fahad Ismail - Ahmad H.Osman, Rahmah; Saad Abdul Rahman Mula, Eman (IIUM JOURNALS, INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA, 2021)
In modern literary studies, the use of modern critical approaches based on the sciences of linguistics and style has become widespread, as tools and methods of criticism and analysis, in light of the separate indications and cues of critics about the inability of traditional rhetoric to penetrate and comprehend the areas of art in modern literature. This is a critical study of a modern literary work that relies on the classical rhetorical lesson as a tool for criticism, and a criterion on which it relies in its judgment and evaluation of the work of art. In his novel "Birds of Taji"; Kuwaiti novelist Ismail Fahd Ismail applies rhetorical methods and images to describe, critic and analyse. This study highlights and analyses how the different ways in which the classical Arabic rhetorical terminologies and styles were utilized and applied throughout the novel.